Cost-benefit analysis of African Risk Capacity informs future implementation of sovereign disaster risk financing for African Union Member States - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The African Risk Capacity (ARC) helps African Union Member States respond early to disasters by providing parametric insurance, combined with regional risk pooling and contingency planning. CGIAR research conducted a cost-benefit analysis of ARC using innovative methods to evaluate ARC policies. Findings and recommendations from this cost-benefit analysis were disseminated to ARC staff and its external board in 2020. ARC welcomed the cost-benefit analysis and ARC is currently exploring ways to implement the recommendations for future program implementation.